Study of the Potential for Using Virtual Reality (VR) Technology in Reducing Pain and Anxiety During Childbirth: A Systematic Literature Review - Widiyastuti, Rika (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Childbirth is a natural physiological process, but it can cause significant pain and anxiety for the mother. Labor pain can have a negative impact on the health of the mother and fetus, while anxiety can worsen the pain and slow down the labor process. Virtual reality (VR) technology is a non-pharmacological method that has the potential to reduce pain and anxiety during labor. This study aims to examine the potential of using VR technology to reduce pain and anxiety during childbirth. Methods: This research was conducted using a systematic literature review method. The search and article selection process was carried out through the Google Scholar and PubMed search engines. Article inclusion criteria are research articles that use quantitative methods, are published in scientific journals, and are in English or Indonesian. Results: The research results show that VR technology can reduce pain and anxiety during labor. Labor pain can be reduced by up to 20%, while anxiety can be reduced by up to 50%. VR technology can work by diverting the mother's attention from pain and anxiety, as well as increasing the production of endorphins, which function as natural analgesics. Conclusion: VR technology is a potential method for reducing pain and anxiety during labor. VR technology can be a safe and effective alternative non-pharmacological method for reducing pain and anxiety during labor.